2013
DOI: 10.1111/1460-6984.12023
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to conversation with semantic dementia: using enactment as a compensatory strategy in everyday social interaction

Abstract: Background Studies to date in semantic dementia have examined communication in clinical or experimental settings. There is a paucity of research describing the everyday interactional skills and difficulties seen in this condition. Aims To examine the everyday conversation, at home, of an individual with semantic dementia. Methods & Procedures A 71-year-old man with semantic dementia and his wife were given a video camera and asked to record natural conversation in the home situation with no researcher pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
1
54
0
Order By: Relevance
“…In their single case study of a man with svPPA, Kindell, Sage, Keady, and Wilkinson (2013) acknowledge that little is known about the communication difficulties and strengths in conversation of people with PPA nor how these strengths and weaknesses impact interaction with the person's family members. This study examined the everyday conversation of the participant and concluded that although neuropsychological assessment revealed severe language impairment, he had developed an adaptive strategy of enactment (acting out/performing meaning) that was relatively effective in conversation.…”
Section: Conversation In Ppamentioning
confidence: 99%
“…In their single case study of a man with svPPA, Kindell, Sage, Keady, and Wilkinson (2013) acknowledge that little is known about the communication difficulties and strengths in conversation of people with PPA nor how these strengths and weaknesses impact interaction with the person's family members. This study examined the everyday conversation of the participant and concluded that although neuropsychological assessment revealed severe language impairment, he had developed an adaptive strategy of enactment (acting out/performing meaning) that was relatively effective in conversation.…”
Section: Conversation In Ppamentioning
confidence: 99%
“…Whilst there has been interest in whether such in‐depth study of conversation could be developed into interventions (Chatwin , Kindell et al . , Perkins et al . , Taylor et al .…”
Section: Introductionmentioning
confidence: 99%
“…Dementia, by contrast, is generally considered a result of widespread multifocal pathology, and it involves dissolution of cognitivel function in which language forms an essential feature (Mathews, Obler & Albert, 1994). There are also dementia diagnoses that share many features with aphasia, such as semantic dementia/semantic primary progressive aphasia (Neary et al, 1998;Kindell et al, 2013). Pursuing research with separate diagnostic groups has made it possible for researchers to study for example correlations between focal brain damages and specific language symptoms.…”
Section: Introductionmentioning
confidence: 99%